2004
DOI: 10.1111/j.1365-2648.2003.02975.x
|View full text |Cite
|
Sign up to set email alerts
|

A concept analysis of palliative care in the United States

Abstract: The scope of palliative care has evolved to include a wide range of patient populations who may not be appropriately termed 'dying' but for whom alleviation of suffering and improvement of quality of life may be very relevant goals. The ultimate success of the new models of palliative care will eventually rest upon the commitment of health professionals to recognize and integrate the changing concept of palliative care into everyday practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0
12

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(113 citation statements)
references
References 60 publications
4
97
0
12
Order By: Relevance
“…Previous studies have reported similar views of nurses and physicians [21,25] and recognition of the stigma attached to palliative care [18].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Previous studies have reported similar views of nurses and physicians [21,25] and recognition of the stigma attached to palliative care [18].…”
Section: Discussionmentioning
confidence: 83%
“…Health care professionals and researchers suggest earlier referral would be more beneficial to provide support and to reduce emotional and spiritual needs well in advance of their death and to establish trust in the patient and their family and acceptance of the nurse [1,2,18].…”
Section: Discussionmentioning
confidence: 98%
“…In the last century, necessary steps were taken toward providing an open comprehension of the burdens of mortal illness, through lessening the taboo against talking about dying, 1 and recognizing the dimensions-physical, social, emotional, and spiritual-of "total pain." 2 Expansions of the palliative care/hospice concept subsequent to these foundations have included interdisciplinary teamwork, 3 initiating care earlier in the disease trajectory, 4 and promoting opportunities for development at end of life. 5 All of these advances set the stage for reaching new possibilities, but there has been no widely accepted theory-driven practical schema to guide interdisciplinary teams toward realizing potential achievements of selfactualization and transcendence.…”
Section: Introductionmentioning
confidence: 99%
“…As of 2015, there are 17 centers affiliated with the Ministry of Health serving as palliative care centers with a total bed capacity of 228 in Turkey. This developing approach of care is also a new concept for health care disciplines that will offer service (Meghani, 2004;Turkish Social Security Institution General Directorate of General Health Insurance, 2015).…”
mentioning
confidence: 99%